2021
DOI: 10.1177/0008417421994967
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Web-Based Time-Use Intervention on Occupational Balance During the Covid-19 Pandemic

Abstract: Background. Restrictions implemented to control the spread of the Covid-19 pandemic may lead to disruptions in occupational balance among university students. Purpose. The aim of this study was to evaluate the effectiveness of a web-based time-use intervention on the occupational balance of university students. Method. A total of 60 participants were randomly assigned to the intervention and control groups. The intervention group received eight sessions of web-based time management intervention, while the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
(38 reference statements)
0
8
0
7
Order By: Relevance
“…In relation to these, it was found that a 4‐week mindfulness intervention significantly improved sleep quality, decreased sleep latency, and decreased sleep problems of undergraduates (Smit & Stavrulaki, 2021; Weis et al., 2021). Additionally, it was found that time management sessions rendered a significantly better balance between work, home, family, leisure, rest, and sleep (Pekçetin & Günal, 2021). Engaging in more physical activity was also found to be associated with better sleep quality (Giner‐Murillo et al., 2021; Martínez‐Lezaun et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In relation to these, it was found that a 4‐week mindfulness intervention significantly improved sleep quality, decreased sleep latency, and decreased sleep problems of undergraduates (Smit & Stavrulaki, 2021; Weis et al., 2021). Additionally, it was found that time management sessions rendered a significantly better balance between work, home, family, leisure, rest, and sleep (Pekçetin & Günal, 2021). Engaging in more physical activity was also found to be associated with better sleep quality (Giner‐Murillo et al., 2021; Martínez‐Lezaun et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, scientific findings on COVID-19 are unequivocal: daily physical and social distancing can impact mental and physical health of populations ( Cao et al, 2020 ; Ransing et al, 2021 ). More specifically, lockdown periods, social distancing, and reducing or even stopping non-essential activities created a real and deep transformation in daily living routines and participation in meaningful occupations ( Cellini et al, 2020 ; King et al, 2020 ; Pekçetin and Günal, 2021 ). Between non-essential needs and essential needs, the complex act of eating became a source of distress, partly because fear of gaining weight was already pervasive and lockdowns led to increased availability of stock-up food at home, which could foster overeating and binge eating episodes ( Phillipou et al, 2020 ; Scarmozzino and Visioli, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Telerehabilitation, which can be delivered with information and communication technology, represents an innovative approach to overcoming the barriers associated with face-to-face (FF) interventions (Hung and Fong, 2019; Negrini et al, 2020). Telerehabilitation technologies provide access to healthcare services at the patient’s home or other settings (Hung and Fong, 2019; Pekçetin and Günal, 2021). Rehabilitation services in the natural environment of the home have the advantage of making treatment more realistic and more applicable in ADLs (Hung and Fong, 2019; Negrini et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, researchers have determined that occupational therapy interventions applied with the TR method are positively effective in regulating time management in university students, improving performance in daily living activities in adult individuals after TKA in the acute period, improving functions, and increasing participation in adolescents with myelomeningocele. (Pekçetin and Günal, 2021; Torpil and Kaya, 2021; Steinhart et al, 2020).…”
Section: Introductionmentioning
confidence: 99%